Assessing genetic counselors' experiences with physician aid‐in‐dying and practice implications. Issue 1 (28th January 2019) - D'Angelo, Abby; Ormond, Kelly E.; Magnus, David; Tabor, Holly K.
Abstract: Physician aid‐in‐dying (PAD) is now legalized in more than half a dozen states across the United States yet remains controversial among health care providers and the general public. Previous studies have described physicians' and nurses' experiences with and attitudes about PAD; however, there is no data about PAD in the context of genetic counseling. This study explores genetic counselors' experiences, understanding, training, and perspectives about PAD. Fifteen participants were recruited to complete semistructured telephone interviews. Five participants had received patient inquiries about PAD. Most participants ( n  = 10) did not feel prepared to discuss PAD with patients and felt that they did not have adequate knowledge to answer patient questions about the practice. Participants described how the unique training, skills, and experiences of genetic counselors could be beneficial for discussing PAD with patients, in comparison to other providers. All participants supported training for genetic counselors about PAD, with many suggesting integration with education about palliative care and end‐of‐life planning. This is the first study to investigate PAD in the context of genetic counseling. Genetic counselors have had patients ask questions about PAD, want education and access to resources about PAD, and believe they can provide important support and guidance to patients considering PAD in some genetic counseling contexts.